2014 IEEE Conference on Electrical Insulation and Dielectric Phenomena (CEIDP) 2014
DOI: 10.1109/ceidp.2014.6995739
|View full text |Cite
|
Sign up to set email alerts
|

Pre-breakdown arcing and electrostatic discharge in dielectrics under high DC electric field stress

Abstract: Highly disordered insulating materials exposed to high electric fields will, over time, degrade and fail, potentially causing catastrophic damage to devices. Step-up to electrostatic discharge (ESD) tests were performed for two common polymer dielectrics, low density polyethylene and polyimide. Prebreakdown transient current spikes or arcs were observed, using both slow and high speed detection. These pre-ESD discharge phenomena are explained in terms of breakdown modes and defect generation on a microscopic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…There are indications that there is a non-zero threshold field for breakdowns [3,6,7,9,10]. Such a threshold is incorporated in dynamic breakdown models [6,11,12].…”
Section: B Three-parameter Weibullmentioning
confidence: 99%
“…There are indications that there is a non-zero threshold field for breakdowns [3,6,7,9,10]. Such a threshold is incorporated in dynamic breakdown models [6,11,12].…”
Section: B Three-parameter Weibullmentioning
confidence: 99%
“…Increases in current significantly steeper than the ohmic curve do not make sense in terms of Ohm's law (V=IR) for the circuit; these are likely due to the ammeter response to increasingly rapid pre-arcs-so rapid that return to baseline current may not be observed [4,10]. Much, if not all, field enhanced conductivity (which is relatively infrequent in MPG tests) will be below the 10% curve; further, field enhance conductivity is expected to increase supra-linearly with voltage and can therefore be distinguished from breakdown.…”
Section: Breakdown Voltage Can Be Defined As the Average Voltage Betwmentioning
confidence: 99%
“…When our test system was first used, the prearcing events were dismissed as noise. Upon closer inspection, it became clear that these events are clearly above the system noise and that the pre-arcing behavior changes from material to material [4].…”
Section: B Comments On Pre-arcingmentioning
confidence: 99%
“…Several pre-arc events have been measured using a fast oscilloscope simultaneously with the ammeter (inset of Fig. 1) [4]. The arcs observed with the oscilloscope had widths of ≲5 μs (this may have been limited by the RC time constant of the measurements circuit) as compared to the ammeter's response time of ~0.5 s This demonstrated that a single large amplitude pre-arc signature in the ammeter data can actually be multiple smaller fast pre-arcs integrated over the ammeter's data response time.…”
Section: B Comments On Pre-arcingmentioning
confidence: 99%
See 1 more Smart Citation